Innovating Arabic Learning Media Through Gender-Responsive Educational Videos - Bella, Sinta; Mahrus Helmi, Achmad; Muhyidin, Muhyidin; Syafiudin, Syafiudin (IJIE International Journal of Islamic Education, 2025)
This study examines the development of Arabic learning video media that integrates gender equality values for students at the vocational or high school level. So far, gender representation in Arabic learning media tends to be biased, with stereotypical role visualizations between men and women. The focus of this research is to design and evaluate gender-responsive learning videos, especially in conversation materials in Arabic. This research uses a qualitative approach with phenomenological methods and interpretivism paradigms. Data was collected through observation, interviews, and documentation, and tested for validity using source triangulation. The results of the study show that there are four values of gender equality that have been successfully integrated in video media, namely: control, access, benefits, and participation. The developed videos not only improve Arabic comprehension, but also provide an equal and inclusive learning experience for both male and female students. This study contributes to enriching value-based foreign language learning media innovations, as well as providing an initial model for the development of gender-fair learning media.